The Mediating Role of Green Accounting Management on Financial Performance: Integrated Stakeholder Theory and Natural Resource-Based View - Ahmad, Ibrahim; Abdullah, Abdullah; Khalik, Abdul; Putra, Aditya Halim Perdana Kusuma (International Journal of Energy Economics and Policy, 2025)
This study investigates the impact of Integrated Environmental Policy (IEP) and Industrial Ecosystem Adaptability and Strategic Environment (IEAS) on Financial Performance (FP) through Green Accounting Management (GAM) as a mediating variable. The research applies the Stakeholder Theory and the Natural Resource-Based View (NRBV) Theory to understand how environmental strategies influence corporate financial outcomes. Data was collected from seven major banks, and the analysis was conducted using structural equation modeling (SEM) to assess direct, indirect, and total effects. The findings demonstrate that IEP significantly affects GAM, and GAM in turn has a substantial impact on FP. Additionally, the results confirm that IEP and IEAS directly influence FP, with GAM playing a key mediating role. Specifically, IEP’s dimension environmental regulation, environmental incentives, environmental monitoring and assessment, and community empowerment—positively influence GAM, which in turn improves financial performance. Similarly, IEAS, with its dimensions of industry competition level, industrial environmental properties, and industrial resilience, shows a significant effect on GAM and subsequently on FP. The study suggests that effective integration of environmental policies and the adaptability of the industrial ecosystem, through GAM, can enhance a company’s financial performance. By applying the Stakeholder Theory, it underscores the importance of considering various stakeholders’ interests, while the NRBV Theory emphasizes the strategic use of environmental resources for long- term competitiveness. These findings provide valuable insights for policymakers and business leaders seeking to leverage environmental strategies for both sustainability and profitability. This research contributes to the existing literature by highlighting the pivotal role of Green Accounting Management as a mediating factor in the relationship between environmental strategies and financial performance, offering practical implications for the banking industry and beyond.